Assessment of Phenology and Productivity of Dual-Purpose Barley Varieties as Affected by Sowing Time and Fodder Harvesting Date: Phenology and yield of barley under different sowing and harvesting times - Singh, Magan; Avinash Chauhan; Supriya (Journal of Cereal Research, 2025)
For assessing the growth and yield of dual-purpose barley, a field experiment was conducted during two consecutive Rabi season to evaluate the green fodder and grain yield of barley (Hordeum vulgare L.) varieties as affected by sowing time and stage of harvesting at the research farm of Forage Research and Management Centre, National Dairy Research Institute, Karnal. The field experiment was laid out in split-split plot design with four treatments of date of sowing (21st October, 31st October, 10th November and 20th November) in main plots, three varieties (RD-2552, RD-2035 and RD-2715) in sub plots and three stage of harvesting (45DAS, 55DAS and 65DAS) in sub-sub plots with three replications. Green fodder and dry matter yield was the highest on 10th November (18.47 t ha-1, 2.17 t ha-1) sowing, variety RD-2715 (17.6 t ha-1, 2.06 t ha-1) and harvesting of fodder at 65 DAS (25.06 t ha-1, 2.98 t ha-1). Grain yield was the highest on 21st October (3.82 t ha-1) sowing date, variety RD 2552 (3.66 t ha-1) and harvesting of fodder at 45 DAS (3.68 t ha-1). Keywords: Dry matter, Fodder yield, Grain yield, Livestock, Spike, Test weight, Tillers